Outward Bound - Hughes, Sheila Hassell (UnderCurrents: Journal of Critical Environmental Studies, 1997)
I could choose to rest, to glory in the smooth glacial slopes of isolation my form reflected on the arctic's deep I could abide on ice floes glowing [...]